UJI GLUKOSA DARAH ANTARA METODE HEKSOKINASE DENGAN GLUKOSA OKSIDASE DAN GLUKOSA DEHIDROGENASE DI DIABETES MELITUS - Baharuddin Baharuddin; Asvin Nurulita; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Diabetes mellitus is a group of metabolic diseases characterized by chronic hyperglycemia that occurs because of abnormalities insulinsecretion, insulin or both. Diabetes mellitus diagnosis is established on the basis of examination of blood glucose levels. The recommendedblood glucose test is enzymatic method by hexokinase using venous blood plasma, while for monitoring the outcomes of treatment: bloodglucose test can be done by rapid test using capillary blood. The purpose of this study was to know the test result of blood glucose betweenhexokinase method (ABX Pentra 400), glucose oxidase (StatStrip Xpress, Super Glucocard II) and glucose dehydrogenase methods(Accu-Chek Performa) by comparing them Cross sectional study was conducted on 50 samples of patient hospitalized at Dr. WahidinSudirohusodo Hospital Makassar. The blood glucose test were performed at the Departement of Clinical Pathology from June up to July2012. Each plasma sample was tested using ABX Pentra 400, StatStrip Xpress, Super Glucocard II and Accu-Chek Performa. The datawere analyzed using Kolmogorov Smirnov and Mann Whitney test. Based from this study was showed that there was no difference in bloodthe level using a related (glucose) oxidase (StatStrip Xpress, Super Glucocard II) and its dehydrogenase method (Accu-Chek Performa)compared with hexokinase method (ABX Pentra 400) with p value > 0.05. The result obtained in this study showed that StatStrip Xpress,Super Glucocard II and Accu-Chek Performa can be used as a rapid test for monitoring blood glucose in hospitalized patients.